Ajmaline, Oxindole, and Cytotoxic Macroline–Akuammiline Bisindole Alkaloids from Alstonia penangiana - Yeap, Joanne Soon Yee; Navanesan, Suerialoasan; Sim, Kae Shin; Yong, Kien Thai; Gurusamy, Subramaniam; Lim, Siew Huah; Low, Yun Yee; Kam, Toh Seok (American Chemical Society, 2018)
Examination of the EtOH extract of the Malayan Alstonia penangiana resulted in the isolation of 10 new alkaloids, comprising two ajmaline (1, 2), four macroline oxindole (3-6), and four macroline-akuammiline bisindole alkaloids (7-10). The structures of these alkaloids were determined based on analysis of the spectroscopic data and, in the case of the oxindole 6 and the bisindole alkaloid 7, also confirmed by X-ray diffraction analysis. The bisindole alkaloids 7 and 8 showed pronounced in vitro growth inhibitory activity against an array of human cancer cell lines, including KB, vincristine-resistant KB, PC-3, LNCaP, MCF7, MDA-MB-231, HT-29, HCT 116, and A549 cells with IC50 values in the 0.3-8.3 μM range.